Indo-European anthropological and cultural sources of the Ossetian heroic epic as an example of nomadism of ideas and values (problem statement): Индоевропейские антропологические и культурные источники осетинского героического эпоса как пример номадизма идей и ценностей (к постановке проблемы) - Dudziak, Arkadiusz; Payunena, Marina (Przegląd Wschodnioeuropejski, 2019)
The paper makes an attempt to analyse the Indo-European cultural categories in the dimension of anthropological and cultural sources which have constituted the national epic of Ossetians, the descendants of the legendary Sarmatian Alans. As a result of studying the present state of knowledge about nomadism, the authors propose a way of understanding that concept as an intercultural penetration of ideas and values through the cultural texts (myths, literary works) in the history of the Indo-European family of Eurasian nations. The authors present the nomadism of Indo-European cultural elements which emerge from the studies of Galina Bieliakowa on Slavic mythology. The article discusses the nomadism of Indo-European ideas, values and cultural symbolism in the context of contemporary anthropological and archaeological knowledge. The authors focus on the phenomenon of preserving the Indo-European cultural heritage in the mythology of the North Caucasus (e.g. the Ossetian heroic epic). The authors also show the phenomenon of the literary image of the sword as an archetypal symbol of honor and purity on the example of the nomadism of that cultural image from the Caucasian epic to the medieval knight epic.